Host long noncoding RNAs in bacterial infections - Cheng, Yong; Liang, Yurong; Tan, Xuejuan; Liu, Lin (Frontiers in Immunology, 2024)
Bacterial infections remain a significant global health concern, necessitating a comprehensive understanding of the intricate host-pathogen interactions that play a critical role in the outcome of infectious diseases. Recent investigations have revealed that noncoding RNAs (ncRNAs) are key regulators of these complex interactions. Among them, long noncoding RNAs (lncRNAs) have gained significant attention because of their diverse regulatory roles in gene expression, cellular processes and the production of cytokines and chemokines in response to bacterial infections.The host utilizes lncRNAs as a defense mechanism to limit microbial pathogen invasion and replication. On the other hand, some host lncRNAs contribute to the establishment and maintenance of bacterial pathogen reservoirs within the host by promoting bacterial pathogen survival, replication, and dissemination. However, our understanding of host lncRNAs in the context of bacterial infections remains limited. This review focuses on the impact of host lncRNAs in shaping host-pathogen interactions, shedding light on their multifaceted functions in both host defense and bacterial survival, and paving the way for future research aimed at harnessing their regulatory potential for clinical applications.